2021
DOI: 10.1155/2021/9932442
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interaction between Mitochondria and the Extracellular Matrix in the Development of Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a condition which affects mainly older adults, that suggests mitochondrial dysfunction and oxidative stress, which follow cells senescence, and might contribute to the disease onset. We have assumed pathogenesis associated with crosstalk between the extracellular matrix (ECM) and mitochondria, mainly based on mitochondrial equilibrium impairment consisting of (1) tyrosine kinases and serine-threonine kinase (TKs and ST-Ks) activation via cytokines, (2) mitochondrial elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 105 publications
(149 reference statements)
0
11
0
Order By: Relevance
“…Although numerous related studies have been reported, the mechanisms underlying the onset and development of IPF remain unclear (37). Epithelialmesenchymal transition, ECM deposition and lung remodelling may be involved in the onset and progression of IPF (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous related studies have been reported, the mechanisms underlying the onset and development of IPF remain unclear (37). Epithelialmesenchymal transition, ECM deposition and lung remodelling may be involved in the onset and progression of IPF (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…The pathological mainly includes the excessive proliferation and/or apoptosis resistance of PASMCs as well as the accumulation of extracellular matrix components such as collagen and elastin. Mitochondria as the central guardian of mitochondrial homeostasis orchestrate diverse cellular processes including cell cycle progression, mitochondrial dynamics, the cell metabolism, and even the extracellular matrix components [ 27 , 28 ], which closely connected the pathogenesis and pathology of PAH. TUFM serves as an important factor in the translational expression of mitochondrial DNA and plays a key role in the control of mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…A deficiency in the synthesis of the mitochondrial-encoded subunits of the respiratory chain alters the ECM composition in cartilage tissue, resulting in collagen crosslinking and an increased ECM stiffness [ 12 ]. The ability of mitochondria to adapt to mechanical stressors in the microenvironment has also been associated with several pathologies, reviewed elsewhere [ [13] , [14] , [15] ]. Organ-on-a-chip or tissue-on-a-chip in combination with microfluidics maintain the integrity of the sample preserving organelle function.…”
Section: Processes Affecting Mitochondrial Dimensionsmentioning
confidence: 99%